A critical realist exploration of the culture of resistance in educational technology integration practices at a South African university - Tshuma, Nompilo (Rhodes University, Faculty of Commerce, Department of Information Systems, 2019)
This thesis seeks to address a number of troubling concerns related to research and practice in the field of educational technology in South African higher education. Firstly, educational technology research has been criticised for a lack of theoretical rigour resulting in perspectives that are tightly focused mostly on practice but fail to adequately interrogate the socio-political complexities of integrating educational technology. Secondly, while research in the field has been criticised for failing to adequately contextualise the study of educational technology, it also fails to interrogate the impact of colonial legacies and Western-developed technologies on integration practices. Thirdly, there seems to be a disconnect between academics' practices and choices with educational technology, and the expectations and assumptions of educational technologists. As such, this thesis predominantly follows inductive reasoning where literature and theory are applied to the empirical situation retrospectively in order to avoid the potential influences and biases of mostly Western-driven discourses on educational technology integration practices. Critical realism is used to 'underlabour' this study. This meta-theory asserts that there are multiple perspectives of an independent reality, and the work of research is to use these perspectives to draw closer to an understanding of that reality. As such, it allows me to interrogate my perspectives firstly, and secondly those of my research participants, about factors that constrain educational technology integration in the South African context through the use of theory (abstract concepts) and data (research participants' multiple perspectives). However, critical realism is somewhat cautious in how to access this reality. Therefore, a critical ethnographic epistemology is employed to strengthen critical realism's aim of accessing knowledge. A critical epistemology emphasises exposing hidden power structures, value judgements as well as self-knowledge and reflexivity. The thesis thus shows how a critical realist ontology could be complemented by a critical ethnographic methodology, particularly in critically-orientated research that has an emancipatory focus which seeks to uncover the socio-political context within which educational technology practices take place. A key argument is that critical realism can be employed as an ontological underlabourer for critical research because of: 1) its immanent critique of traditionally-accepted philosophies, 2) its emphasis on critique of our knowledge claims and value judgements, 3) its insistence that knowledge of the social world necessarily precedes emancipation, and 4) its different conceptions of power (oppressive power and transformatory power). This critical ethnographic research is conducted in a South African university with eight female academics. Data collection is in the form of interviews, observations and reflections, as well as informal and work-related interactions. At each data collection moment, I have had to be reflexively aware of my positionality as an educational technologist, the impact of a colonially-motivated methodology and an ethically-aware approach that seeks to put the needs of the research participants first. Critical ethnography's meaning-making and critical realism's abduction and retroduction are used to analyse and make sense of the data. In my attempt to contextualise the study's findings, I first uncover structural forces and their impact on the academic role before attempting to correlate this with educational technology practices. The study's findings point to two main structural forces in the socio-political context of South African higher education: the teaching/research tension and the elevation of one dominant culture. In terms of the teaching/research tension, the female academics in this study have to balance the urgent teaching function with the valued research function. They struggle to find this balance because of ambiguous messages from different structures, their passion for teaching, oppressive departmental dynamics and the pressures of their career trajectory. The elevation of one dominant culture is demonstrated through both oppressive cultural practices and untransformed curricula. The study shows that academics mitigate these structural constraints mostly through subtle every day resistance that seeks to mitigate their effect on both the academics and, where applicable, their students. Archer's morphogenetic/morphostatic cycle is used retrospectively, in response to fieldwork, to conceptualise why this resistance comes about. A resistance framework developed using Archer is then used to understand educational technology choices and practices. The results of the research show that while academics are often pictured as resistant to technology as a response to different barriers, they actually often employ technology to resist structural forces. That is, with this thesis I show that there is a focus on resistance with technology rather than resistance to technology. The study shows how the research participants resist structural forces (teaching tension and dominant culture) by using technology to create safe and responsive learning spaces. As such, this thesis challenges educational technologists to re-think the way they support academics by recommending support strategies that acknowledge both the structural forces in the South African higher education context, as well as the culture of resistance, both of which impact academics' educational technology choices and practices.
Keywords: Critical realism; Educational technology -- South Africa; Education, Higher -- Effect of technological innovations on -- South Africa; College teachers -- South Africa; College teaching -- Sociological aspects -- South Africa